Present and Future Detection of Terrestrial Biomarkers on Earthshine. Issue Volume 8:Issue S293(2012) (29th April 2014) - Briot, Danielle; Arnold, Luc; Jacquemoud, Stéphane; Schneider, Jean
Abstract: In the context of life detection on terrestrial exoplanets, new methods of search for spectral signatures of chlorophyll and other biomarkers in the Earthshine have been developed in the last few decades. Astronomical observations made at OHP and ESO (NTT) showed a significant signal when continents are facing the Moon. This signal, called the Vegetation Red Edge (VRE), is undoubtedly due to chlorophyll absorption properties. In order to strengthen these results, the LUCAS (LUmière Cendrée en Antarctique par Spectroscopie) project dedicated to the measurement of the Earthshine from the Concordia Research Station (C Dome, Antarctica) has been set up. One of the objectives of LUCAS was to observe prolonged variations of the VRE corresponding to various parts of the Earth facing the Moon. An extension of this project, called LUCAS II, would allow long-term observations to detect seasonal variations of the vegetation signal. These data, together with accurate measurements of the Earth's albedo, will help validate a model of global and spectral albedo of our planet.